Thallium Pollution in Europe Over the Twentieth Century Recorded in Alpine Ice: Contributions From Coal Burning and Cement Production. Issue 13 (12th July 2022) - Legrand, Michel; McConnell, Joseph R.; Preunkert, Susanne; Bergametti, Gilles; Chellman, Nathan J.; Desboeufs, Karine; Plach, Andreas; Stohl, Andreas; Eckhardt, Sabine
Abstract: Emission inventories indicate that thallium, a highly toxic metal, is emitted during coal burning and cement production. These estimates have been established only for the 1980s and 1990s but up to now they have not been compared to long‐term observations. Here we used alpine ice cores to document thallium pollution over Europe since ∼1850. Ice‐core thallium concentrations increased from 1890 to 1910, and decreased after 1965 to concentrations that were half 1890 levels. Comparison of ice‐core trends, estimated past emissions, and state‐of‐the‐art atmospheric aerosol transport modeling suggest that coal burning was responsible for thallium pollution in Europe, particularly from 1920 to 1965 because of high coal consumption at that time. The subsequent decline resulted from decreased coal consumption and reduced emissions following technological improvements. The ice‐core data suggest that the rapid growth of cement production that took place in Europe after 1950 had a limited impact on thallium pollution. Plain Language Summary: Although less prevalent in the environment than toxic metals such as lead and cadmium, thallium is a highly toxic metal even at very low levels. Because reliable measurements are difficult at such low concentrations, thallium pollution is far less documented than other toxic metals. Cement production originally was estimated to be the primary source of thallium pollution at the global scale, but it was later recognized that coal burning was likely the main source. These previous estimates refer to the recent decades but no longer‐term inventories were available. Furthermore, no inventories were established at the scale of the European continent. Detailed measurements in Alpine ice cores show that thallium pollution after the late 19th century primarily was the result of coal burning in western Europe, and was largest between 1920 and 1965 as expected from coal consumption records. The rapid growth of cement production that took place after World War II had only limited impact on thallium pollution in Europe. Key Points: Alpine ice core data indicate thallium pollution in western Europe since ∼1850 Emissions from growing cement production after World War II contributed little to European thallium pollution Anthropogenic thallium emissions in western Europe were dominated by coal burning throughout the 20th century